Clinical Efficacy of Medicinal Plants Formulations for the Prevention of Androgenetic Alopecia in Korean Individuals - Kaushik, Neha; Chang, Ihseop; Park, Suhyeon; Sohn, Youngju; Choi, Kyung-A; Park, Young Kum; Wonkyu, Wonkyu; Kim, June-Hyun (Brazilian Journal of Case Reports, 2025)
Androgenetic alopecia (AGA) is the most prevalent form of nonscarring alopecia, characterized by a distinct pattern of gradual hair loss. Despite its non-lethal nature, AGA can exert a profound psychosocial impact, particularly on women and younger men, affecting their quality of life. Standard therapeutic approaches for AGA commonly involve the use of finasteride and minoxidil; however, these treatments are often associated with adverse side effects, particularly with prolonged use. In this study, we present the successful management of AGA in a cohort of Korean individuals, comprising both male and female subjects (totaling 52 participants, with 12 exclusions). Significant reductions in the affected AGA area were observed across the cohort, yielding highly satisfactory outcomes. These findings suggest that the treatment modality employed in this study offers a promising alternative for AGA management in the population, demonstrating efficacy irrespective of gender.